Implicações do rompimento da barragem de Fundão nos usos da água e da terra na bacia do Alto Rio Doce - MG - Nayara Mariana Gonzaga Rosa (2020)
Considered as one of the biggest socio-environmental disasters in Brazilian history, the Fundão tailings dam failure (in November / 2015) which is owned by the mining company Samarco (joint venture between Vale SA and BHP Billiton) resulted in the release of approximately 43,7 million m³ of iron ore tailings, which followed 660km of waterways in the Rio Doce drainage basin. The impacts stemming from the event, however, presented differentially throughout the affected area. After following Santarém stream, Gualaxo do Norte river, Carmo river and the upper course of Doce river, the tailings wave reached the reservoir of Risoleta Neves Hydroelectric Power Plant, in which the lower energy regime resulted in the deposition of a large portion of transported solids. After crossing the Risoleta Neves dam, the fine-grained waste was carried by the Doce River without imposing significant changes to marginal areas. As a result of this process, in the area between the Fundão dam and the hydroelectric power plant, the tailings caused silting of watercourses, mischaracterization of river channels, and morphological changes in floodplains. Therefore, this area can be singled-out as the most impacted in the entire drainage basin. Even after five years, the damage caused by the dam failure has not yet been fully investigated, especially considering its long-term consequences. Given this context, this study aimed to identify the main changes in water and land uses resulting from the collapse of the Fundão tailings dam in Mariana, Barra Longa, Rio Doce, and Santa Cruz do Escalvado municipalities, which integrate the area between the rupture point and the Risoleta Neves Hydroelectric Power Plant. As specific objectives, the research sought to understand the main challenges in meeting the social demands related to water and land from the perspective of managers and users. Besides that, the study aimed to spatialize the main changes identified in the area, considering the pre- and post-rupture scenarios, and investigate the effectiveness of the institutional design created to achieve the repairing objectives in the affected territories. To reach the determined goals, methodological procedures were carried out, organized in three main stages: (i) literature and secondary data research; (ii) survey of primary information based on field work and interviews with representatives of the main social sectors involved in the matter; and (iii) treatment of data / information and consolidation of results. The results obtained demonstrate that the Fundão dam failure caused significant changes in water and land use in the investigated municipalities, which represent important impacts on the quality of life of the affected populations. With regard to meeting demands, significant failures were observed. These failures are related to the ways of conducting the recovery process and the political-institutional organization created for this purpose.